Chemical unlocking method for Micro LED integrated packaged COB panels

CN116466215BActive Publication Date: 2026-10-09LEDMAN OPTOELECTRONIC HZ CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310279187.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-20
Publication Date
2026-10-09
Estimated Expiration
2043-03-20

AI Technical Summary

Technical Problem

[0004]机械方法使用打磨或雕刻剔除等机械物料,逐层小心去除外封胶,直到裸露出LED晶片,机械方法没有引入其它物质,方便分析晶片表面成份,且不用破坏整个失效样品,保留了驱动电路便于通电检查,还具有操作简单、耗材成本低的优势,但是需要引入高温、去胶的过程,容易损伤键合线,需要依赖人员的熟练度,人力成本高

Benefits of technology

[0008] The beneficial effects of the present invention are as follows: The chemical unsealing method of the present invention involves attaching an adhesive film to the COB panel to protect the panel, then creating a dam on top of the adhesive film, removing the adhesive film in the dam and injecting a dissolving solution to dissolve the encapsulating adhesive, thereby completing the unsealing. This chemical unsealing method does not require cutting the COB panel and does not affect the failure analysis of Micro LEDs, and can effectively unseal individual failed pixels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116466215B_ABST
    Figure CN116466215B_ABST
Patent Text Reader

Abstract

The present application relates to a chemical opening method, in particular to a chemical opening method of a Micro LED integrated packaging COB panel. The chemical opening method comprises the following steps: pasting a layer of adhesive film on the COB panel, then making a ring dam above the adhesive film at a failure point, removing the adhesive film in the ring dam and injecting a dissolving solution into the ring dam to dissolve the packaging adhesive, and then cleaning with anhydrous ethanol and drying to complete the opening. The chemical opening method does not need to cut the COB panel, does not affect the failure analysis of the Micro LED, and can effectively open the single failure pixel point.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a chemical opening method, and more particularly to a chemical opening method for Micro LED integrated packaged COB panels. Background Technology

[0002] In micro LEDs, pixels composed of R, G, and B pixels are integrated and encapsulated in the light-emitting surface above the display panel. The size of the unit board, pixel pitch density, and bonding positions in the encapsulation process are directly proportional. Taking a 60.8*17.1mm unit board as an example, assuming a pixel pitch of 1.2 and a resolution of 48*135, the calculated pixel count is 6480, requiring 19440 chips, 97200 bonding lines, and 194400 bonding positions. Common failure phenomena of unit boards include: single point or series of lights not lighting, dim lighting, and misaligned lighting. If a panel has more than 3 failure points, the entire unit board often needs to be scrapped. Many failures are reflected on the light-emitting surface, but visual inspection after opening the package cannot directly identify the cause of the problem; a driving signal is still needed to check the electrical and optical performance of the failure point.

[0003] COB (Chip On Board) panels directly package the chip onto the PCB board. Unlike discrete LED devices that can be easily removed from the PCBA through desoldering, COB failure unit boards, if the failure pixel location is cut out for analysis, can easily damage the drive circuitry, hindering the identification and confirmation of faults. Failure analysis techniques are divided into destructive and non-destructive analysis. Destructive analysis of COB panels can use chemical or mechanical methods to open the package.

[0004] Mechanical methods use grinding or carving tools to carefully remove the outer sealant layer by layer until the LED chip is exposed. Mechanical methods do not introduce other substances, making it easy to analyze the chip surface composition. They do not destroy the entire failed sample, preserving the drive circuit for easy power-on inspection. They also have the advantages of simple operation and low consumable costs. However, they require high temperatures and a desmearing process, which can easily damage the bonding wires. They also rely on the skill of the personnel, resulting in high labor costs.

[0005] Chemical methods use a solvent (sulfuric acid or a special solution) to immerse and dissolve the outer sealant on the LED chip surface of failed COB panel samples over a specific time and temperature. Chemical methods are highly reliable, do not rely excessively on human skill, and allow for complete observation of the encapsulation process morphology, bond line morphology, and breakage locations. However, current chemical methods require cutting the COB panel, destroying the entire failed sample. Chinese invention patent CN102509693A discloses a chemical unsealing method for aluminum wire-connected plastic-encapsulated electronic components. This method involves first wrapping the sample to be unsealed with tin foil to expose a localized area, then using concentrated sulfuric acid at 180–250°C to etch and unseal the localized area. While this method avoids cutting, it requires continuously applying the hot etching solution to the sample using a dropper, a cyclical manual operation. Furthermore, the high temperature of concentrated sulfuric acid poses a significant risk and can easily affect the circuitry, resulting in low accuracy in failure analysis. Summary of the Invention

[0006] In order to overcome the shortcomings of the prior art, the technical problem to be solved by the present invention is to provide a chemical unpacking method for Micro LED integrated packaged COB panels that can be effectively unpacked without cutting the COB panel.

[0007] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is: a chemical unpacking method for Micro LED integrated packaged COB panels, wherein a layer of adhesive film is attached to the COB panel, a dam is made above the adhesive film at the failure point, the adhesive film in the dam is removed and a dissolving liquid is injected into the dam, and the unpacking is completed after dissolution.

[0008] The beneficial effects of the present invention are as follows: The chemical unsealing method of the present invention involves attaching an adhesive film to the COB panel to protect the panel, then creating a dam on top of the adhesive film, removing the adhesive film in the dam and injecting a dissolving solution to dissolve the encapsulating adhesive, thereby completing the unsealing. This chemical unsealing method does not require cutting the COB panel and does not affect the failure analysis of Micro LEDs, and can effectively unseal individual failed pixels. Attached Figure Description

[0009] Figure 1 The diagram shown is a structural schematic of a failed Micro LED integrated package COB sample according to Embodiment 1 of the present invention.

[0010] Figure 2 The diagram shown is a schematic diagram of the adhesive film after being bonded according to Embodiment 1 of the present invention;

[0011] Figure 3 The diagram shown is a schematic diagram of the situation after sulfuric acid injection in Embodiment 1 of the present invention;

[0012] Figure 4 The diagram shown is a schematic diagram of the first embodiment of the present invention after opening;

[0013] Figure 5 The image shown is a diagram illustrating the effect of powering on Embodiment 1 of the present invention. Detailed Implementation

[0014] To explain in detail the technical content, objectives, and effects of the present invention, the following description is provided in conjunction with the embodiments and accompanying drawings.

[0015] The most crucial concept of this invention lies in: attaching an adhesive film to the COB panel to create a dam, removing the adhesive film from the dam, and injecting a dissolving solution to dissolve the encapsulating adhesive, thus completing the chemical opening.

[0016] Please refer to Figures 1 to 4 As shown, the chemical unpacking method for the Micro LED integrated packaged COB panel of the present invention involves attaching a layer of adhesive film to the COB panel, then creating a dam around the adhesive film at the failure point, removing the adhesive film in the dam and injecting a dissolving solution into the dam, and completing the unpacking after dissolution.

[0017] As can be seen from the above description, the beneficial effects of the present invention are as follows: a protective film is attached to the COB panel, a dam is made above the film, the film in the dam is removed and a dissolving solution is injected to dissolve the encapsulating adhesive, thus completing the opening. This chemical opening method does not require cutting the COB panel and does not affect the failure analysis of Micro LEDs. It can effectively open individual failed pixels.

[0018] During the dissolution process, depending on the needs of the analysis, the encapsulating adhesive of the failed sample is partially dissolved, completely dissolved, or dissolved layer by layer. During the dissolution process, the layers are observed one by one. The first layer exposed is the arc top C area of ​​the red light crystal bonding line, followed by the surface layer of the blue and green crystal and the bonding point A area, and finally the bonding lines D and E areas and the PAD position of the PCB.

[0019] Furthermore, the specific steps for applying the adhesive film are as follows: at room temperature, cut an area of ​​10*10 to 30*30mm for the adhesive film and apply it to the COB panel with the failure point as the center. After application, press it three times.

[0020] As can be seen from the above description, the function of the adhesive film is to protect the pixels in the non-failed areas from reacting with the solvent.

[0021] Furthermore, the adhesive film is PE tape or PET high-temperature tape.

[0022] As can be seen from the above description, the adhesive film must have at least the following properties: the adhesive film leaves no residue, does not tear unused epoxy adhesive, is not corroded by sulfuric acid, and does not shrink, melt, or deform at a high temperature of 80 degrees Celsius.

[0023] PE tape (polyethylene, abbreviated as PE) is a thermoplastic resin obtained by polymerizing ethylene. PET high-temperature tape is made of PET coated with acrylic adhesive on both sides. The tape is generally transparent, with common thicknesses ranging from 0.05 to 0.2 mm. It has a long-term temperature resistance of 100-120°C and a short-term temperature resistance of up to 140-200°C. Both PE tape and PET high-temperature tape meet the film requirements of this invention.

[0024] Furthermore, the specific steps for making the dam are as follows: with the failure point as the center, use hot melt adhesive to make an irregular, near-circular dam above the adhesive film at the failure point. The height of the dam is ≥2mm and the inner diameter is >4mm.

[0025] As described above, the height of the dam should be ≥2mm to allow for the injection of an appropriate amount of dissolving solution without damaging undamaged pixels. There should be no leakage at the edges, and the dam removal should not easily damage the light-emitting surface. The inner diameter of the dam should be >4mm to ensure that the dam does not cover the exposed encapsulating adhesive.

[0026] Furthermore, the hot melt adhesive is made of EVA resin.

[0027] As can be seen from the above description, the dam material used in this application needs to take into account several factors: first, it has different material properties from the encapsulating adhesive and is not corroded by the solvent; second, it can be cured and formed at room temperature for rapid sample preparation; and third, it has good high-temperature stability.

[0028] Hot melt adhesive is a thermoplastic adhesive that is solid at room temperature but liquefies at higher temperatures. The molten liquid wets the substrate, and when the adhesive layer cools and hardens, a bond is formed. The melting temperature is generally 65℃ to 180℃. When the base resin of hot melt adhesive is EVA resin (ethylene and vinyl acetate copolymerized under high temperature and pressure), it has excellent corrosion resistance, resisting corrosion from chemicals such as salts, acids, and alkalis, and can withstand immersion in concentrated sulfuric acid at 80℃ for 24 hours; good hot workability, processed at 150-200℃, easy to hot press, cut, apply, and bond; excellent stability, not softening at around 80℃; and good chemical stability, aging resistance, and ozone resistance, meeting the requirements of this application for dam materials.

[0029] Furthermore, the specific steps for removing the adhesive film in the dam are as follows: taking the failure point as the center, remove the adhesive film with a square area of ​​approximately 1*1 to 2*2 mm.

[0030] As described above, removing the adhesive film in the dam allows the dissolving solution to contact the encapsulating adhesive at the failure point. Controlling the size of the removed adhesive film prevents the pixels in the non-failed areas from reacting with the dissolving solution.

[0031] Furthermore, the solution is concentrated sulfuric acid with a mass fraction of 98.3%.

[0032] As described above, sulfuric acid is a high-boiling-point, non-volatile strong acid with strong corrosiveness. Concentrated sulfuric acid with a mass fraction of 98.3% has a melting point of 10℃ and a boiling point of 338℃. It is suitable for a wide range of encapsulating adhesives, has low material costs, and offers low dissolution temperature and fast dissolution speed.

[0033] Furthermore, the amount of the dissolving solution used is 0.5 to 1 mL.

[0034] As can be seen from the above description, the amount of solution used is limited to prevent the solution from overflowing the dam.

[0035] Furthermore, the melting temperature during dissolution is 3–10°C lower than the melting point of the dam.

[0036] As can be seen from the above description, if the dissolution temperature is too high, it will not only cause excessive corrosion and damage to the failed sample due to the too fast dissolution rate, but it will also melt the surrounding dam and cause leakage of the dissolution solution; if the dissolution temperature is too low, the dissolution rate will be slow and affect the efficiency of opening the package.

[0037] Furthermore, after dissolution, the opened COB panel is cleaned and dried using anhydrous ethanol.

[0038] As can be seen from the above description, cleaning with anhydrous ethanol and drying after dissolution can clean away the residual solution and prevent electromigration and electrochemical corrosion from damaging the sample again when electricity is applied.

[0039] Please refer to Figures 1 to 4 As shown, Embodiment 1 of the present invention is as follows:

[0040] A chemical unlocking method for Micro LED integrated packaged COB panels involves laminating an adhesive film onto the COB panel, including the following steps:

[0041] S1: Take a COB panel sample with a single point failure and an outer sealant thickness of 400um. Cut a 20*20mm area PE tape or PET high-temperature tape at room temperature and attach it to the COB panel with the failure point as the center. Press it three times after bonding. The outer sealant material is epoxy resin without silica and the TG point is about 130 to 160 degrees.

[0042] S2: Centered on the failure point, use a hot melt glue gun to create an irregular, near-circular dam with EVA resin above the adhesive film at the failure point; the dam is 2mm high, 5mm in inner diameter, the hot melt glue gun has a power of 300W, a temperature of 200℃, and an inner diameter of 1mm for the nozzle.

[0043] S3: Using the failure point as the center, use a blade to remove a square area of ​​adhesive film of approximately 1.5*1.5mm.

[0044] S4: Inject 0.7 mL of 98.3% concentrated sulfuric acid into the dam, place the sample in the test chamber to dissolve the failed sealant, keep the temperature in the test chamber constant at 61.3℃, and dissolve for 2 hours;

[0045] S5: Manually and mechanically peel off the remaining film and dam, then use anhydrous ethanol for ultrasonic cleaning and drying to complete the opening.

[0046] After opening the COB panel, connect the electrical signal to power it on. The effect after powering on is shown in the image. Figure 5 ,Depend on Figure 5 It can be seen that the COB panel opened by the chemical opening method of the present invention can drive the circuit to facilitate power-on inspection and achieve effective opening.

[0047] Embodiment 2 of the present invention is as follows:

[0048] A chemical unlocking method for Micro LED integrated packaged COB panels involves laminating an adhesive film onto the COB panel, including the following steps:

[0049] S1: Take a COB panel sample with a single point failure and an outer sealant thickness of 300um. Cut a 10*10mm area PE tape or PET high-temperature tape at room temperature and attach it to the COB panel with the failure point as the center. Press it three times after bonding. The outer sealant material is epoxy resin without silica and the TG point is about 130 to 160 degrees.

[0050] S2: Centered on the failure point, use a hot melt glue gun to create an irregular, near-circular dam with EVA resin above the adhesive film at the failure point; the dam is 3mm high, 6mm in inner diameter, the hot melt glue gun has a power of 300W, a temperature of 200℃, and an inner diameter of 1mm for the nozzle.

[0051] S3: Using the failure point as the center, use a blade to remove a square area of ​​adhesive film of about 1*1mm.

[0052] S4: Inject 0.5 mL of 98.3% concentrated sulfuric acid into the dam, place the sample in the test chamber to dissolve the failed sealant, the temperature of the test chamber is 60℃, and the dissolution time is 1 hour;

[0053] S5: Manually and mechanically peel off the remaining film and dam, then use anhydrous ethanol for ultrasonic cleaning and drying to complete the opening.

[0054] Embodiment 3 of the present invention is as follows:

[0055] A chemical unlocking method for Micro LED integrated packaged COB panels involves laminating an adhesive film onto the COB panel, including the following steps:

[0056] S1: Take a COB panel sample with a single point failure and an outer sealant thickness of 500um. Cut a 30*30mm area PE tape or PET high-temperature tape at room temperature and attach it to the COB panel with the failure point as the center. Press it three times after bonding. The outer sealant material is epoxy resin without silica and the TG point is about 130 to 160 degrees.

[0057] S2: Centered on the failure point, use a hot melt glue gun to create an irregular, near-circular dam with EVA resin above the adhesive film at the failure point; the dam is 2mm high, 5mm in inner diameter, the hot melt glue gun has a power of 300W, a temperature of 200℃, and an inner diameter of 1mm for the nozzle.

[0058] S3: Using a blade, remove approximately 2*2mm square areas of adhesive film centered on the failure point.

[0059] S4: Inject 1 mL of 98.3% concentrated sulfuric acid into the dam, place the sample in the test chamber to dissolve the failed sealant, the temperature of the test chamber is 63℃, and the dissolution time is 3h;

[0060] S5: Manually and mechanically peel off the remaining film and dam, then use anhydrous ethanol for ultrasonic cleaning and drying to complete the opening.

[0061] In summary, this invention provides a chemical unsealing method that involves bonding an adhesive film to the COB panel to protect unaffected pixels from reacting with the dissolving solution. A dam is then created above the adhesive film, the film within the dam is removed, and the dissolving solution is injected to dissolve the encapsulating adhesive, completing the unsealing process. This chemical unsealing method eliminates the need to cut the COB panel and does not interfere with Micro LED failure analysis, enabling effective unsealing of individual failed pixels. Compared to existing methods using aluminum foil wrapping, this invention eliminates the need for handheld components and high-temperature dissolving solutions. The unsealing temperature is around 60 degrees Celsius, avoiding any adverse effects from high-temperature stress. Furthermore, this method offers better and more convenient protection than aluminum foil wrapping, eliminating defects such as scratches and incomplete wrapping.

[0062] During the dissolution process, depending on the analytical requirements, the encapsulating adhesive of the failed sample is partially dissolved, completely dissolved, or dissolved layer by layer, and the process is observed layer by layer.

[0063] The dissolution temperature should be controlled to be 3-10°C lower than the melting point of the dam. If the dissolution temperature is too high, it will not only cause excessive corrosion and damage to the failed sample due to the too fast dissolution rate, but it will also melt the dam and cause leakage of the dissolution liquid. If the dissolution temperature is too low, the dissolution rate will be slow and affect the efficiency of opening the seal.

[0064] After dissolving, the sample is cleaned with anhydrous ethanol and dried to remove any residual solution and prevent electromigration and electrochemical corrosion from damaging the sample again when electricity is applied.

[0065] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent modifications made based on the content of the present invention's specification and drawings, or direct or indirect applications in related technical fields, are similarly included within the patent protection scope of the present invention.

Claims

1. A chemical unlocking method for Micro LED integrated packaged COB panels, characterized in that, A layer of adhesive film is adhered to the COB panel, and then a dam is made above the adhesive film at the failure point. The adhesive film in the dam is removed and a dissolving liquid is injected into the dam. After dissolution, the opening is completed. The adhesive film is PE tape or PET high-temperature tape. The dam is made of EVA resin using hot melt adhesive.

2. The chemical unlocking method for Micro LED integrated packaged COB panels according to claim 1, characterized in that, The specific steps for applying the adhesive film are as follows: at room temperature, cut an area of ​​10*10~30*30mm for the adhesive film and apply it to the COB panel with the failure point as the center. After application, press it down.

3. The chemical unlocking method for a Micro LED integrated packaged COB panel according to claim 1, characterized in that, The specific steps for making the dam are as follows: taking the failure point as the center, use hot melt adhesive to make an irregular, roughly circular dam above the adhesive film at the failure point. The height of the dam is ≥2mm and the inner diameter is >4mm.

4. The chemical unlocking method for a Micro LED integrated packaged COB panel according to claim 1, characterized in that, The specific steps for removing the adhesive film in the dam are as follows: take the failure point as the center and remove the adhesive film with a square area of ​​1*1~2*2mm.

5. The chemical unlocking method for a Micro LED integrated packaged COB panel according to claim 1, characterized in that, The solution is concentrated sulfuric acid with a mass fraction of 98.3%.

6. The chemical unlocking method for a Micro LED integrated packaged COB panel according to claim 1, characterized in that, The amount of the dissolving solution used is 0.5~1mL.

7. The chemical unlocking method for a Micro LED integrated packaged COB panel according to claim 1, characterized in that, The melting temperature during dissolution is 3-10°C lower than the melting point of the dam.

8. The chemical unlocking method for a Micro LED integrated packaged COB panel according to claim 1, characterized in that, After the dissolution is complete, the opened COB panel is cleaned and then dried with anhydrous ethanol.

Citation Information

Patent Citations

  • Chemical unsealing method of plastic package electronic component using aluminum wire as connecting wire and preparation method of etching solution used in chemical unsealing method

    CN102509693A

  • Method of assembling chips

    US20050194695A1

  • Adhesive tape for resin-encapsulating and method of manufacture of resin-encapsulated semiconductor device

    US20110111563A1